2008
DOI: 10.1007/s12355-008-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Relative performance of the sugarcane families in early selection stages

Abstract: Family selection is widely used in early stages of selection in sugarcane breeding programs. Families are evaluated in the first one or two stages of selection and individual clones are selected from within superior families. These selected clones are evaluated for their performance in two or three selection stages before commercial release of superior clones. This study was undertaken to assess the relative performance of five sugarcane families for predicting potential parental combinations and also to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License the next selection stages have also been reported (Skinner et al, 1987;Cox and Hogarth, 1993;Shanthi et al, 2008;Stringer et al, 2010;Mahmoud et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License the next selection stages have also been reported (Skinner et al, 1987;Cox and Hogarth, 1993;Shanthi et al, 2008;Stringer et al, 2010;Mahmoud et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
“…44, 128.63, 115.11, 103.88, 103.69, 102.74 and 100.53% of the mean of the check cultivar ROC22 (22.74 ton/hectare), respectively. These were the best crosses across all other bi-parental crosses for most studied traits either in plant cane or in first ratoon crops, suggesting the possibility of evaluation of a large number of clones of these bi-parental crosses, followed by selection of superior clones within these crosses during the next selection stages (Skinner et al, 1987;Cox and Hogarth, 1993;Shanthi et al, 2008;Stringer et al, 2010;Mahmoud et al, 2012). Data in Figure 2 showed that the highest infection with mosaic showed by the check cultivar ROC22 so, all families were more resistance than the check variety and all families do not show any infection by smut.…”
Section: Selected 10% Selection Intensity Based On Tshmentioning
confidence: 99%
“…Some authors have already showed that the use of family selection contributes to parental selection, in addition to mating, which aim to obtain improved populations (Kimbeng and Cox, 2003;Shanthi et al, 2008). The strategy of family selection has been previously used in some sugar cane improvement projects in Brazil (Leite et al, 2009;Pedroso et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These include standard breeding, molecular marker assisted selection, disease monitoring, adjustment of management practices, fungicide applications, and selection of rust resistant cultivars in the breed program by intensive rust screening [23]. Studies have shown that parents producing progeny with a high frequency of transgressive segregates for agronomic traits should provide the best opportunity for sugarcane breeders to select clones superior to their parents [36]. In addition to directly evaluating parental lines for brown rust and other diseases, therefore, parental evaluation based on their progeny performance for rust resistance and other agronomic traits in the early clonal stage of a sugarcane breeding program should help optimize parental selection and crossing combinations.…”
Section: Relationships Between Brown and Orange Rustsmentioning
confidence: 99%
“…In addition to directly evaluating parental lines for brown rust and other diseases, therefore, parental evaluation based on their progeny performance for rust resistance and other agronomic traits in the early clonal stage of a sugarcane breeding program should help optimize parental selection and crossing combinations. Studies have suggested that family selection is effective in improving sugarcane populations in early selection stages [36][37][38][39], because it can identify those families that harbor the highest proportion of desirable clones and makes it possible to focus on selection for superior clones [36]. Availability of family data for rust diseases and agronomic traits helps sugarcane breeders improve crossing combinations for developing genotypes with resistance to rusts and high yields.…”
Section: Relationships Between Brown and Orange Rustsmentioning
confidence: 99%